2002
DOI: 10.1248/bpb.25.1623
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Skin Barrier Function Using Direct Current II: Effects of Duty Cycle, Waveform, Frequency and Mode.

Abstract: The aim of this study was to evaluate the reduction in skin barrier function caused by pulsed iontophoresis by measuring resistance in the short term. Experiments under direct current (DC) and pulsed direct current (PDC) conditions were carried out using rat abdominal skin in vivo. The resistance was measured every 62.5 m ms and analyzed using a two-compartment model consisting of surface and skin resistance. Moreover, the initial value and the rate constant of surface resistance were calculated with the non-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The results reported in Fig. 2 demonstrate that rat skin impedance after shaving was about 1,200 W. This value is compatible with the age of the rats used in these experiments, given that skin resistance in rats increases with aging (17), and it is also compatible with values determined in Wistar male rats where abdominal hair was clipped (18). Abrasion significantly (p < 0.05 vs. Bcontrol^) reduced rat skin impedance.…”
Section: Resultssupporting
confidence: 84%
“…The results reported in Fig. 2 demonstrate that rat skin impedance after shaving was about 1,200 W. This value is compatible with the age of the rats used in these experiments, given that skin resistance in rats increases with aging (17), and it is also compatible with values determined in Wistar male rats where abdominal hair was clipped (18). Abrasion significantly (p < 0.05 vs. Bcontrol^) reduced rat skin impedance.…”
Section: Resultssupporting
confidence: 84%
“…On the one hand, the efficiency of iontophoretic transport depends on the quantity of current delivered (i.e. product of intensity by time) (Kalia et al, 2004), but on the other hand it also depends on the effect of the current itself on the electrical properties of the skin (Chen and Chien, 1996;Chizmadzhev et al, 1998;Kanebako et al, 2002aKanebako et al, , 2003Kanebako et al, , 2002bNair and Panchagnula, 2004). In particular, it is known that using a relatively high voltage during iontophoresis facilitates the transport of drugs by a mechanism of pore formation which decreases the skin's resistance (Glaser et al, 1988;Sims et al, 1992;Inada et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Recent fundamental studies have also suggested that hbFGF is a potent inhibitor of terminal mesodermal differentiation and the formation of myofibroblasts and thus may have a role in the treatment of keloids; current therapeutic approaches involve direct injection into these areas of hyperproliferative growth which can be painful. , The specific iontophoretic conditions, including the current density, duration and profile of current application and the application area, which influence hbFGF delivery must be optimized, but the results presented here point to the feasibility of administering therapeutic amounts of hbFGF. Although clinical studies involving continuous or pulsatile iontophoresis of both low molecular weight therapeutics and peptides for 24 h have been reported and shown that iontophoretic patches were well-tolerated, local administration of the protein would require shorter, perhaps intermittent, application periods; this has been suggested as a means to reduce the risk of local irritation. , …”
Section: Discussionmentioning
confidence: 99%